Mechanistic characterization of nitrite‐mediated neuroprotection after experimental cardiac arrest. Issue 3 (3rd October 2016) - Dezfulian, Cameron; Kenny, Elizabeth; Lamade, Andrew; Misse, Amalea; Krehel, Nicholas; St. Croix, Claudette; Kelley, Eric E.; Jackson, Travis C.; Uray, Thomas; Rackley, Justin; Kochanek, Patrick M.; Clark, Robert S. B.; et al.
Abstract: Nitrite acts as an ischemic reservoir of nitric oxide (NO) and a potent S‐nitrosating agent which reduced histologic brain injury after rat asphyxial cardiac arrest (ACA). The mechanism(s) of nitrite‐mediated neuroprotection remain to be defined. We hypothesized that nitrite‐mediated brain mitochondrial S‐nitrosation accounts for neuroprotection by reducing reperfusion reactive oxygen species (ROS) generation. Nitrite (4 μmol) or placebo was infused IV after normothermic (37°C) ACA in randomized, blinded fashion with evaluation of neurologic function, survival, brain mitochondrial function, and ROS. Blood and CSF nitrite were quantified using reductive chemiluminescence and S‐nitrosation by biotin switch. Direct neuroprotection was verified in vitro after 1 and 4 h neuronal oxygen glucose deprivation measuring neuronal death with inhibition studies to examine mechanism. Mitochondrial ROS generation was quantified by live neuronal imaging using mitoSOX. Nitrite significantly reduced neurologic disability after ACA. ROS generation was reduced in brain mitochondria from nitrite‐ versus placebo‐treated rats after ACA with congruent preservation of brain ascorbate and reduction of ROS in brain sections using immuno‐spin trapping. ATP generation was maintained with nitrite up to 24 h after ACA. Nitrite rapidly entered CSF and increased brain mitochondrial S‐nitrosation. Nitrite reduced in vitro mitochondrial superoxide generation and improved survival of neurons after oxygen glucose deprivation. Protection was maintained with inhibition of soluble guanylate cyclase but lost with NO scavenging and ultraviolet irradiation. Nitrite therapy results in direct neuroprotection from ACA mediated by reductions in brain mitochondrial ROS in association with protein S‐nitrosation. Neuroprotection is dependent on NO and S ‐nitrosothiol generation, not soluble guanylate cyclase. Abstract : We examined the mechanism whereby early nitrite therapy is protective after resuscitation from asphyxial cardiac arrest. We found that nitrite rapidly crosses the blood–brain barrier and S‐nitrosates mitochondrial proteins with associated reductions in superoxide (O2 − ) and peroxide (H2 O2 ) generation. Using pharmacologic inhibition studies in a neuronal oxygen glucose deprivation model, we demonstrated that nitrite‐mediated protection is dependent on nitric oxide (NO) formation and cysteine S‐nitrosation rather than the classical soluble guanylate cyclase (sGC) pathway.